2015
DOI: 10.14814/phy2.12292
|View full text |Cite
|
Sign up to set email alerts
|

Long-term methionine-diet induced mild hyperhomocysteinemia associated cardiac metabolic dysfunction in multiparous rats

Abstract: Mild hyperhomocysteinemia (HHcy, clinically defined as less than 30 μmol/L) is an independent cardiovascular disease (CVD) risk factor, and is associated with many complications during pregnancy, such as preeclampsia (PE). The aim of this study was to assess the effect of long-term mild HHcy on cardiac metabolic function of multiparous rats. Female rats were mated 3 to 4 times and were fed with methionine in drinking water to increase plasma Hcy (2.9 ± 0.3 to 10.5 ± 2.3 μmol/L) until termination. This caused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…8A). In agreement with previous studies (33,34,43), administration of BK to normal hearts stimulated NO release to suppress oxygen consumption, a response that spares oxygen to potentiate exercise tolerance. However, the BK-induced NO-mediated suppression of MV O 2 was basically indiscernible in myocardium of rats in the HF- 30D group (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…8A). In agreement with previous studies (33,34,43), administration of BK to normal hearts stimulated NO release to suppress oxygen consumption, a response that spares oxygen to potentiate exercise tolerance. However, the BK-induced NO-mediated suppression of MV O 2 was basically indiscernible in myocardium of rats in the HF- 30D group (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…If the plasma levels of Hcy exceed 10–15 μmol/l, there is a condition known as hHcy, which occurs as a result of an inborn error of methionine metabolism or by non-genetic causes [ 35 ]. In our experiment, in the Met-C group was the level of Hcy increased 1.5-fold in comparison to the naïve control animals that matches the criteria for mild hHcy [ 35 , 36 ]. Dos Santos et al [ 37 ] demonstrated in their hHcy model (subcutaneous injection of DL-Hcy in the lower dose of 0.03 μmol/g of the body weight of male Wistar rats twice a day for 30 days that this dose increases rats Hcy plasma concentration, similarly described in the moderate hHcy patients.…”
Section: Discussionmentioning
confidence: 74%
“…High methionine intake and/or hyperhomocysteinemia have also been shown to upregulate major cellular oxidant systems, including NAD(P)H oxidases [90-95]. NAD(P)H oxidases, also known as NOX enzymes, are a family of enzymes contributing to age-related increases in ROS production in cells of the cardiovascular and immune systems as well as other organs [93, 165,166]. In the context of high methionine intake and hyperhomocysteinemia, increased NAD(P)H oxidase activity can further exacerbate age-related oxidative stress [93,165].…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%